2015
DOI: 10.1007/s10037-015-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Labor migration and overeducation among young college graduates

Abstract: This paper focuses on labor market outcomes of young college graduates in the US, analyzing the nexus between migration, overeducation, and economic conditions. A series of overeducation probit models are estimated, using data from the March Supplements of the Current Population Survey, 2000-2014. We find that labor migrants are less prone to being overeducated as unemployment rates increase. For stayers, in contrast, we find a positive link between overeducation propensities and unemployment rates. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The number of nonmovers appears large because we do not include intra‐municipal moves. Due to the set‐up of our data, we cannot observe hem, but moreover these arguably concern moves with a residential rather than a work‐related motive, which is found to be an important distinction (Waldorf & Yun, ). We also include squared terms in our analysis .…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…The number of nonmovers appears large because we do not include intra‐municipal moves. Due to the set‐up of our data, we cannot observe hem, but moreover these arguably concern moves with a residential rather than a work‐related motive, which is found to be an important distinction (Waldorf & Yun, ). We also include squared terms in our analysis .…”
Section: Methodsmentioning
confidence: 85%
“…Regional and individual productivity is maximized if graduates are able to fully exploit their talents by achieving a good match on the labor market. At the individual level, spatial mobility is sometimes necessary to escape from a lack of suitable job opportunities, as an inferior match early in the career may have negative longer‐term consequences (Brunner & Kuhn, ; Waldorf & Yun, ). Recent graduates have been found to be particularly spatially mobile, since, following graduation, they seek to achieve a good match on the labor market to obtain a high return on their educational investment (Hensen, De Vries, & Cörvers, ; Iammarino & Marinelli, ; Venhorst, Van Dijk, & Van Wissen, ).…”
Section: Literature Review: the Return On Spatial Mobilitymentioning
confidence: 99%
“…These dimensions have been extensively investigated in relation to Italian or U.K. university undergraduates, and several studies have reported that migration favours a good education–job match (Abreu et al, 2015; Croce & Ghignoni, 2015; Devillanova, 2013; Di Cintio & Grassi, 2013), especially when it involves a move from Southern to Northern regions (Iammarino & Marinelli, 2015). Similarly, looking at U.S. college graduates, it has been shown that migration reduces labour overeducation, especially in time of crisis (Waldorf & Do Yun, 2016), and it is more likely to occur toward geographical areas that offer employment opportunities that fit and reward graduate's competencies (Winters, 2017). Further, data on young people from Britain and Australia indicated that human capital migration, especially long‐distance migration, increases job satisfaction (Perales, 2017).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Chapter 2: Conceptualising Routes and Outcomes 42 often promoted by events such as divorce, widowhood and retirement Green 2010, Waldorf andDo Yun 2016), and leads to increased risk of economic instability and lifestyle changes in the year following the move (Geist and McManus 2008). This wide range of non-economic drivers behind migration decisions can obscure the complexity of migration processes, which provides additional rationale behind the need for more understanding of graduate migration beyond the assumption of the ERT.…”
Section: Internal Migrationmentioning
confidence: 99%
“…As shown in previous section of this chapter, this group of movers are most likely to have moved more than once and their geographical mobility is inconsistent with the assumptions of the ERT theory. Under the assumptions of ERT, this might imply that complex movers are least likely to prioritise their social mobility, and might have been driven by other than economic reasons, such as divorce or widowhood Green 2010, Waldorf andDo Yun 2016).…”
Section: Complex Moversmentioning
confidence: 99%